Developing competitive marketing strategies : a case study of the Garuda Indonesia Airline - Muchsin; Johri, Lalit M.; Swierczek, F.W.; Bechter, Clemens; The Government of Austria (Bangkok : Asian Institute of Technology, 1997)
The airline industry is currently facing a number of longer term challenges from market liberalization, industry restructuring thorough mergers, acquisition and strategic alliances to rapid technological changes. An airline company requires competitive marketing strategy as the technology alone is not enough for competition. This study is intended to search and analyze external factors and internal factors of Garuda Indonesia to help this company develop its competitive marketing strategy. In depth interviews with key personnel in marketing department have been conducted. In addition, a sample of 100 passengers have been taken at the CengkarengJ akarta International airport to support this study. Questionnaire has been designed for the passengers. Garuda Indonesia, an airline of Indonesia, is a fully state-owned company. Since its inception, this company has been the agent of the development. As the agent of development, Garuda Indonesia is expected to accelerate the economic development of the country by bringing as many tourists as possible to Indonesia. With this program, Garuda Indonesia has participated in the opening job creation to indigenous people. As a consequence of competitive challenges, Garuda Indonesia in general suffered big losses in 1993, 1994 and 1996. To overcome such big loses, Garuda Indonesia group is encouraged to examine efficiency of its operations. To date, Garuda Indonesia does not have a passenger monitoring committee. Price is the most important factor why passengers choose Garuda Indonesia followed by promotional discount package. Services in terms of speed check-in, entertainment choice, seat space, luggage safety service and baggage allowance service are positive on the eyes of the passengers. However, passengers negative perceptions toward departure punctuality. This has been proved that 86 % of the passengers have experienced the flight delays with Garuda Indonesia in international flights. In addition, flight attendant's performance, food and drinks, level of courtesy are other points that are considered average by the passengers. Toward the end, the author suggests a feasible competitive marketing strategy in both short term and long term perspectives.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration.
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 1997
Keywords: Airlines -- Indonesia -- Marketing